Des solveurs implicites d’ordre supérieur pour les problèmes de dynamique non linéaire des structures - Boutmir, Sanaa; Braikat, Bouazza; Jamal, Mohammad; Damil, Noureddine; Cochelin, Bruno; Potier-Ferry, Michel (European Journal of Computational Mechanics, 2004)
We develop in this work, some implicit temporal high order solvers for solving non linear elastic structural dynamic problems involvingfinite deformations. These solvers are based on the perturbation method, the homotopical transformation and time space discretization techniques. Their accuracy is improved by the introduction of Padé approximants. Numerical calculations, compared with others classical solvers, are illustrated on forced nonlinear vibration problems of a 2D elastic beam and an elastic plate.